Analisis Perbandingan Kinerja Keuangan Sebelum Dan Sesudah Merger pada Perusahaan Non Keuangan yang Terdaftar Di BEI Tahun 2016-2017 - Alvi Nur Aini; Ika Farida Ulfah; Nurul Hidayah (ISOQUANT : Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Because of the creation of a global market by economic globalization, there is intense competition among businesses. As a result, the company is constantly working to grow its  Keywords: Merger, Financial Performance, Financial Ratios